Preconception education program for non-invasive prenatal testing focused on interest in genetics among female university students in Japan: a quasi-experimental study comparing pre-intervention, post-intervention, and three-month follow-up results - Chihiro Katada; Kazutomo Ohashi; Kimie Okada; Hideaki Sawai (BMC, 2023)
Abstract Background Non-invasive prenatal testing (NIPT) is offered as a reproductive choice in many countries. However, pregnant women, particularly those who are primipara or lack knowledge of prenatal testing, experience difficulties understanding adequate information and making decisions on NIPT. This study developed a preconception education program about NIPT, focusing on interest in genetics, and aimed to clarify the effectiveness of the program to help women make decisions on future NIPT. Methods This was a one-group, quasi-experimental, pre-post-test study. The study population was female undergraduate students in Japan who participated in the education program. This program included two games and was based on the Attention, Relevance, Confidence, and Satisfaction (ARCS) model, which is an instructional design that stimulates learning interest and motivation. The data of 73 pre-pregnant women who completed all three questionnaires-before, immediately after, and three months after the intervention-were analyzed to clarify the time effects. Moreover, all variables were analyzed using logistic regression analysis to investigate factors related to decisional conflict. Results Interest in genetics, knowledge of genetics and prenatal testing, and indecisive attitudes toward NIPT significantly improved immediately after the intervention, and consequently, these changes and reduction of decisional conflict were maintained at three months. Moreover, low decisional conflict at follow-up was significantly associated with a high interest in genetics (adjusted odds ratio, 3.42). Conclusions These findings provide preliminary evidence that this preconception education program, which focused on facilitating interest in genetics, assists pre-pregnant women to reduce decisional conflict about future NIPT. Trial registration The trial was registered at the UMIN-CTR registry (January 16, 2023), registration number UMIN000050047.